Hydrodeoxygenation of biomass-derived oxygenates over metal carbides: from model surfaces to powder catalysts. Issue 12 (25th May 2018) - Lin, Zhexi; Chen, Rui; Qu, Zhenping; Chen, Jingguang G.
Abstract : Transition metal carbides are promising catalysts for upgrading biomass derivatives via the hydrodeoxygenation reaction. Abstract : The hydrodeoxygenation (HDO) reaction is critical to the upgrading of lignocellulosic biomass into valuable fuels and chemicals. Many transition metal carbide (TMC) catalysts have been shown to be highly selective toward the C–O/CO bond scission, which makes them promising catalysts for the HDO reaction. This review summarizes the reaction pathways of linear and ring-containing biomass-derived oxygenates over TMC model surfaces and powder catalysts, followed by a discussion on the effect of reaction conditions on reaction pathways. The combination of first principles calculations, model surface experiments, and parallel reactor studies demonstrates the feasibility of using model surface science studies to guide the rational design of efficient catalysts for the upgrading of lignocellulosic biomass derivatives. General trends and future research directions of using TMC catalysts for HDO are also discussed.